P26 Exploring the acceptability and feasibility of using activity monitors to support increased physical activity within an exercise referral scheme for adults with, or at risk of, a chronic health condition. (3rd September 2019) - Kelson, MJ; Hawkins, J; Edwards, M; McConnon, L; Hallingberg, B; Oliver, E; Charles, J; Tudor Edwards, R; Murphy, S; Simpson, S
Abstract : Background: Whilst there is evidence for initial effectiveness of exercise referral schemes for increasing physical activity, evidence of long-term effects is limited. In Wales, a trial of the National Exercise Referral Scheme [NERS] showed small but significant impacts on physical activity at 12-month follow-up. Technologies such as activity monitors may enhance long-term maintenance of activity by facilitating goal setting and progress monitoring and supporting intrinsic motivation. This pilot trial explored the acceptability and feasibility of implementing accelerometry-based activity monitors within NERS. Methods: New NERS participants (mean age=57, 65% female) were randomised to receive either an activity monitor alongside NERS (n=88) or usual practice (n=68). Participants completed questionnaires at baseline, 16-weeks and 52-weeks. Twenty intervention participants and 12 NERS staff completed interviews at 4-weeks and 52-weeks. Results: Findings suggest that participant experiences of utilising the activity monitors were mixed. Approximately half of participants reported that the devices were easy to use (49%) and met their expectations (57%). In interviews, some participants reported that the monitors helped them to become more aware of their physical activity levels and increased their motivation. Barriers to acceptability included general and device-specific wearability and technological problems, such as device malfunctioning and computer compatibility issues. Staff also reported device- and context specific technological barriers to implementing the monitors alongside usual practice. Conclusion: Whilst some findings were device-specific, there are broader lessons for future research and practice incorporating activity monitoring devices into physical activity interventions such as implications for delivery staff time and training.